The anatomy of the arterial supply of the thoracic limb of the porcupine (Hystrix cristata) - Yilmaz, S; Aydin, A; Dinç, G (Blackwell Verlag Gmbh, 2001)
The aim of this study was to investigate the anatomy of the arterial supply and branches of the thoracic limb of the porcupine. With this aim, five (three male and two female) adult porcupines were used. The vascular tree of the thoracic limb was injected through the common carotid arteries with coloured latex. The a. thoracica externa arose from the a. axillaris at the level of the fourth rib. It divided into two branches and went to the in. cutaneus trunci and the in. pectoralis ascendens. The a. subscapularis came off the a. thoracodorsalis. Later, the a. circumflexa humeri caudalis et cranialis, the three muscular branches and the a. circumflexa scapulae arose from the a. subscapularis. The a. profunda brachii arose together with the a. bicipitalis from the same truncus. The a. collateralis ulnaris left from the a. brachialis independently. Rete carpi dorsale was formed by the a. radialis, the r. carpeus dorsalis of the a. collateralis ulnaris and the a. interossea caudalis. Arcus palmaris profundus was formed by the r. profundus of the a. interossea caudalis and the r. palmaris profundus of the a. radialis. In conclusion, despite a partial resemblance to that in the rat, the distribution of the thoracic limb arteries in the porcupine was found to be completely different from that of other mammals. These findings represent, to our knowledge, the first study on the distribution of thoracic limb arteries in the porcupine.